Geotouristic values of the Northwestern Ethiopian Plateau as an opportunity for development - Florek, Wacław; Majewski, Marek (Acta Geographica Lodziensia, 2024)
Various countries and regions are constantly seeking new development opportunities. This is particularly important in areas with low levels of development. Geotourism as a branch of special tourism (sustainable, sightseeing, qualified, environmental) may present such an opportunity, and the geotourist values of the Northwestern Ethiopian Plateau should be treated as a factor conducive to the development of this part of Ethiopia. However, before preparing an offering addressed to specific groups of tourists, it is necessary to develop a catalogue of geotourist resources. This is quite easy for large landforms (the Abyssinian Rift, the Blue Nile Gorge, laccoliths in Tigray), while the recognition of geological values (rocks occurring on the surface of the area and in exposures, mineral deposits) and objects related to human activity in prehistory (e.g., megaliths) and historical times (stelae, churches and monasteries carved in rocks) requires the involvement of well-trained geologists, archaeologists and other specialists. In recent years, considerable progress has been observed in the recognition of the geotourist values of the Northwestern Ethiopian Plateau, as evidenced by numerous publications. There are also studies presenting an offer for those interested in geotourism or geoarchaeology.